Archival theory, chronology and interpretation of rock art in the Western Cape, South Africa - Mguni, Siyakha (Cambridge monographs in African archaeology, 2016)
This work advocates the archival capacity of rock art and uses archival perspectives to analyse the chronology of paintings in order to formulate a framework for their historicised interpretations.